Analysis of Principles and Concepts for Developing Arabic Language Teaching Materials - Sitti Najmianti Rahma Basit; H. Andi Abdul Hamzah (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the concepts and fundamental principles in developing Arabic teaching materials. Using a qualitative descriptive method with a library research approach, data were collected from various literature sources such as books, journals, and relevant articles. The data analysis process included reduction, categorization, and interpretation of the literature, focusing on the principles of curriculum relevance, effectiveness, efficiency, and theoretical approaches such as behaviorism, constructivism, and communicative methods. Data validity was ensured through source triangulation to confirm reliability.The findings indicate that effective Arabic teaching materials must align with the curriculum, support the achievement of student competencies, and be designed effectively and efficiently. Key elements of teaching materials include systematically and attractively organized text, images, exercises, and evaluations. The development of teaching materials based on behaviorist approaches emphasizes behavior modification through repetition and reinforcement, constructivist approaches focus on independent learning and student experiences, while communicative approaches facilitate language use in real-life contexts.This study concludes that well-designed teaching materials adhering to learning principles are essential to support students' success in understanding and mastering content. These findings provide practical recommendations for developing interactive and effective Arabic teaching materials tailored to learning needs.